Penile carcinoma: what dermatologists need to know - Maria J. Guimarães; Rita Macieira; Filomena Azevedo; Carmen Lisboa (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Penile cancer is a rare disease in developed countries and is frequently underrecognized by clinicians leading to delays in diagnosis and treatment. Squamous cell carcinoma (SCC) is the predominant pathological entity, representing 95% of all penile cancers. The most important risk factor for penile SCC is human papillomavirus (HPV) infection, with an estimated prevalence of 50%. Other major risk factors include phimosis, chronic inflammatory dermatosis, and poor genital hygiene. Two major pathophysiologic pathways have been proposed, one linked to HPV and another to chronic inflammation. Penile SCC usually presents as an erythematous area of induration or an ulcerating lesion, although changes can be more subtle in premalignant lesions [PeIN]. Confirmation of the diagnosis by biopsy and histopathological examination should be followed by staging. For localized diseases, namely PeIN, topical immunotherapy, chemotherapy, and epithelial ablative techniques are treatment options. For localized SCC, the mainstay of treatment is complete excision. Radiotherapy can be considered an organ-sparing alternative. The role of chemotherapy in penile SCC remains under discussion. The estimated 5-year overall survival is 66%, varying from 90% for T1N0M0 tumors to < 50% for patients with positive lymph nodes. Clarification of the role of HPV in premalignant lesions and penile SCC pathology has the potential to improve prevention and treatment regimens, namely through vaccination against HPV. Given its rarity and low levels of awareness by both patients and clinicians, penile SCC represents a diagnostic challenge. Prompt diagnosis is key to effective treatment since prognosis in the early stages is excellent.